Effect of age on presentation and outcome in renal colic. Issue 1 (February 2023) - Golomb, Dor; Shemesh, Amit; Goldberg, Hanan; Shalom, Ben; Hen, Eyal; Barkai, Eyal; Atamna, Fahed; Abu Nijmeh, Haitham; Cooper, Amir; Raz, Orit
Objectives: To examine the age-related differences in the presentation, management, and outcomes of patients admitted to the emergency department (ED) with ureteral stones. Patients and methods: A retrospective analysis of all patients who visited the ED at a single institution that were found to have a ureteral stone on CT. Clinical, laboratory, and imaging parameters were collected, including outcomes. Patients were subdivided into age groups: 18–30, 31–50, 51–70, and >70 years. Results: Between January 2018 and December 2020, 778 patients were admitted to the ED with a ureteral stone. About 78% (609) were males and 22% (169) were females. The mean ages were 49.4 (SD 14.4) and 51.6 (SD 15.7) in males and females, respectively ( p  = 0.08). Patients in the 36–50 age group, had significantly higher visual analogue scale (VAS) scores ( p  < 0.0001). Patients older than 70 years old presented with significantly higher serum creatinine levels ( p  < 0.0001), C-reactive protein (CRP) ( p  < 0.001) and leukocyte levels ( p  = 0.002). These patients were also found to have significantly larger stones (mean size of 6.2 mm (SD 4.8) ( p  < 0.0001)) and underwent percutaneous nephrolithotripsy (PCNL) in significantly higher numbers (56.3% vs 43.8%, ( p  < 0.0001)). Less than half of the patients older than 50 years were given medical expulsive therapy (MET) with alpha-blockers, compared to more than 50% in the other age groups ( p  = 0.002). Spontaneous stone expulsion was noted in 70.2% of the 18–35-year group, 62.4% of the 36–50-year-old group, 51.8% of the 51–70-year-old group, and 37% of the >70-year-old group ( p  < 0.0001). The ED re-admission rates at 7 and 30 days were not significantly different among all age groups. Conclusions: Our data suggests that older patients presented with larger stones, elevated inflammatory markers and creatinine and were more likely to require surgical intervention. The spontaneous stone expulsion rate was inversely associated with age.